Bio-connectionist model based in the thalamo-cortical circuit. - Chalita, Mario Andrés; Lis, Diego (Panamerican Journal of Neuropsychology / Cuadernos de Neuropsicología)
Recent studies on the interaction of the thalamus with the neocortex positively feed the intuition that not only the neocortex is primarily responsible for the learning process, but also its intrinsic relationship to the thalamus is. Computer simulation conveniently support the hypotheses derived from these new experimental results. In this paper we argue for the need for an intermediate discipline between the computational cognitive neuroscience and connectionism, which we call bio-connectionism. We present a bio-connectionist model that simulates projections between the thalamus and the neocortex - particularly in the primary sensory area. A new sense of the word memory results from this bio-connectionist design. Finally, through the search of an interpretation of the model results, we contrast it with the work of a first-wave connectionist: W. K. Taylor, who, as a result of profuse contribution to the tradition, published in 1964 guidelines for a model whose assumptions are similar to the model discussed herein. On the neuroscientific level, highlights the importance of the thalamus in its relation to the neocortex and their responsibility in cognitive processes. In relation to connectionism, we present a bio-connectionist model from which a possible explanation for the recent experimental data is derived. From the standpoint of the history of connectionism, we try to show why the work of Wilfred Kenelm Taylor should be reconsidered.